The effectiveness of a training program in Majlis Perbandaraan Johor Bahru Tengah (MPJBT) / Nurul Izzati Shuhada Zulkurnain - Zulkurnain, Nurul Izzati Shuhada (2014)
In this chapter, I am going to discuss about the background of the organization. Majlis Perbandaraan Johor Bahru Tengah (MPJBT) also known as Johor Bahru Tengah Municipal Council. The Johor Bahru Tengah Municipal Council is a local based council which was founded in 1953. It started as a small administration centre which eventually was merged to a Local Council, and'once again, Johor Bahru Tengah has created another history when it was declared as a Local Authority with a Municipal status.